Silek Harimau in the Film Merantau: Representation of Social Identity, Spiritual Values, and Local Tradition of the Minangkabau Community - Abdul Mugni; Bibi Suprianto (Jurnal Studi Agama dan Masyarakat, 2026)
Existing studies on Minangkabau culture have largely examined migration traditions, adat–Islam relations, and local wisdom, yet little attention has been given to the representation of Silek Harimau in film as a medium for constructing social identity, spiritual values, and local tradition. The study aimed to analyze how the film Merantau represents Silek Harimau as part of Minangkabau cultural identity and spirituality of the Merantau tradition. The particular study used a media approach and interviews with various community groups, cultural figures, and observers related to the views of the Silek Harimau. The findings cover several aspects, namely: traveling as a social identity of the Minangkabau people, traveling teaches the existence of spiritual values ​​and local traditions to the Minang people, and the existence of philosophical values ​​in the Silek Harimau. Moreover, the study recommended the importance of interviewing the Minangkabau people. Thus, the Silek Harimau in the film Merantau not only tells the story of social life but also depicts the social, spiritual, and traditional identities that are still maintained by the Minang people.